Draft Genomes Shed Light on the Dual Bacterial Symbiosis that Dominates the Microbiome of the Coral Reef Sponge Amphimedon queenslandica - Gauthier, Marie-Emilie A.; Watson, Jabin R.; Degnan, Sandie M. (Frontiers in Marine Science, 2016)
Amphimedon queenslandica is a coral reef demosponge that houses a low complexity and low abundance microbiota dominated by a proteobacterial duo for which draft genomes are presented here. The most prevalent symbiont, AqS1, is a sulfur-oxidizing gammaproteobacterium closely related to other demosponge symbionts and to free-living Ectothiorhodospiraceae (Chromatiales). The predicted gene repertoire of AqS1 indicates that it is capable of sulfur oxidation, carbon monoxide oxidation and inorganic phosphate assimilation, and that some of its metabolic capabilities may have been acquired via horizontal gene transfer from alphaproteobacteria. The second most prevalent symbiont, AqS2, is a betaproteobacterium whose closest known relatives are other demosponge symbionts. AqS1 has characteristic sponge symbiont features, including a versatile nutrient use with large number of transporters, ankyrin-repeat-containing proteins, and a CRISPR system. Based on the size of its genome assembly, AqS2 is predicted to have a much smaller genome with many fewer symbiotic features than AqS1. The smaller is reflected in its more limited metabolic capabilities that include carbohydrate metabolism, but not sulfur oxidation or phosphorus metabolism. Within-pathway complementation and resource partitioning potentially occur between the two bacteria. The addition of these symbiont genomes to extensive genome and transcriptome resources already available for the sponge host now permits the development of mixed-species genome-scale metabolic models as a foundation for experimental investigations of resource partitioning between symbionts and host.